2021
DOI: 10.14791/btrt.2021.9.e19
|View full text |Cite
|
Sign up to set email alerts
|

Lorlatinib Therapy for Rapid and Dramatic Control of Brain and Spinal Leptomeningeal Metastases From ALK-Positive Lung Adenocarcinoma

Abstract: We report a patient with severe neurological deterioration due to leptomeningeal metastases involving brain and spinal cord from anaplastic lymphoma kinase (ALK)-positive lung adenocarcinoma, managed rapidly and successfully with lorlatinib therapy. A 48-year-old male patient presented with acute mental deterioration, severe headache, and weakness of both legs. The patient’s previous medical history included cerebral metastases from ALK-positive lung adenocarcinoma, which had been successfully managed via whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…(1) EGFRþ: Multiple studies assessing first-and second-generation EGFR-TKIs (gefitinib, erlotinib, afatinib) effect on leptomeningeal metastasis and OS was found to be nearly ]. Lorlatinib, a third-generation ALK-TKI and dual ALK/ ROS1i, has shown intracranial activity in patients with pretreated ALK-positive NSCLC [63] and dramatic responses in case series [64,65]. An international expanded access program of lorlatinib demonstrated that patients with leptomeningeal metastasis (nine ALKþ and two ROS1þ) achieved an intracranial ORR of 45% (95% CI 17-77), and a PFS of 9.3 (95% CI 1.0-NR), OS data were not included [66].…”
Section: Histology Agnostic Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) EGFRþ: Multiple studies assessing first-and second-generation EGFR-TKIs (gefitinib, erlotinib, afatinib) effect on leptomeningeal metastasis and OS was found to be nearly ]. Lorlatinib, a third-generation ALK-TKI and dual ALK/ ROS1i, has shown intracranial activity in patients with pretreated ALK-positive NSCLC [63] and dramatic responses in case series [64,65]. An international expanded access program of lorlatinib demonstrated that patients with leptomeningeal metastasis (nine ALKþ and two ROS1þ) achieved an intracranial ORR of 45% (95% CI 17-77), and a PFS of 9.3 (95% CI 1.0-NR), OS data were not included [66].…”
Section: Histology Agnostic Solid Tumorsmentioning
confidence: 99%
“…In the leptomeningeal metastasis arm ( n = 18), intracranial ORR was 12.5% (95% CI, 0.3–52.7), median PFS was 5.2 months (95% CI, 1.6–7.2) and median OS was 7.2 months (95% CI, 1.6–16.9) [62 ▪ ]. Lorlatinib, a third-generation ALK-TKI and dual ALK/ROS1i, has shown intracranial activity in patients with pretreated ALK-positive NSCLC [63] and dramatic responses in case series [64,65]. An international expanded access program of lorlatinib demonstrated that patients with leptomeningeal metastasis (nine ALK+ and two ROS1+) achieved an intracranial ORR of 45% (95% CI 17–77), and a PFS of 9.3 (95% CI 1.0–NR), OS data were not included [66].…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…Investigation of a German early access program revealed a partial response rate of 77.8% among 9 patients with LM, but did not provide further details regarding duration of response [90]. While these expanded access datasets are limited due to their retrospective nature and lack of protocolized neuraxial assessments, they complement a number of case reports demonstrating improvement of both LM disease burden and neurologic symptoms following lorlatinib treatment [91][92][93].…”
Section: Met Genomic Alterations In Nsclcmentioning
confidence: 99%
“…CSF sampling of 10 total patients treated with lorlatinib 100 mg daily in phase I/II studies revealed a CSF-to-plasma ratio of 0.73 [92] and 0.77 [93], far higher than what had been previously demonstrated for crizotinib. Prospective studies of lorlatinib in patients with LM are lacking, however a phase II subgroup analysis and several case reports in patients with ALK+ LM have highlighted rapid symptom improvement and long-lasting intracranial responses, ranging 8-22 months [88,[94][95][96]. The largest cohort analysis of leptomeningeal activity of lorlatinib derives from an international early/expanded access program of 95 previously TKI-treated patients, in which 11 evaluable patients with LM (9 ALK+ and 2 ROS1+) achieved an intracranial ORR of 45% (95% CI 17-77) and DCR of 91% (95% CI 59-100) [97].…”
Section: Alk Inhibitorsmentioning
confidence: 99%